Perancangan Logo Merek UMKM Lil Pie’s Cang Ijo Menggunakan Semiotika Charles Sanders Pierce - Jovanan Kartiko, Samuel (Jurnal Industri Kreatif dan Inovatif, 2023)
Brand identity is strongly influenced by the existence of the brand logo itself to show the identity and face of abrand. Designing a logo to show brand identity in a new present product is very important where the product canbe known by the public. The logo will identify a brand. The visual signs used the letter marks and pictures markon Lil Pie Cang ijo were designed using the theory of semiotics by Charles Sanders Pierce. Lil Pie Cang ijo doesnot yet have a brand identity, so the logo that will be designed is expected to produce the Lil Pie Cang Ijo logothat can identify the brand and can be known by the public.